Rolling stock planning for passenger transportation - Butkevičius, Jonas; Lingaitis, Leonas P.; Vaičiūnas, Gediminas (Transport, 2004)
The planning of the optimal rolling stock for passenger carriage should be based on passenger flow forecasts, close examination of the available locomotives and cars and properly chosen methods of their writing off and plans for rolling stock renewal. The strategy of renewing the existing rolling stock for passenger transportation (including plans for writing off, modernization and purchasing of cars and locomotives) is offered by the authors which is based on forecasts of passenger flow variation and expenses. First Published Online: 27 Oct 2010